Pollen Morphology and Palynotaxonomical Studies of Common Garden Plants of Apocynaceae, In Kolkata, West Bengal, India - Chatterjee, Reshmi; Sarkar, Satadip; Rao, G. M. Narasimha (International Journal of Environment, 2014)
Taxonomy and identification of angiosperms are mainly based on external morphological characters and traits of the plants; however palynological data sets are remotely used for the study. Pollen characters are genetically regulated that can be used as an ideal tool for establishing taxonomic groups. This type of integrated study can be useful in redefining the status of families in higher group of plants. Apocynaceae, a Eurypalynous family exhibits variation in possessing more than one type of pollen grains from simple porate to compound colporate apertures. Pollen attributes has been utilized in building a pollen key that would enable us to distinguish genera solely on the basis of pollen characters. DOI: http://dx.doi.org/10.3126/ije.v3i4.11735 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 109-116